Kleine schriften = Collected short writings of Josef van Ess - Ess, Josef van. (Islamic History and Civilization, 2017)
Kleine Schriften , written by the eminent German scholar of Islamic Studies Josef van Ess, is a unique collection of Van Ess' widely scattered short writings, journal articles, encyclopaedia entries, (autobiographical) essays, reviews and lectures, in (mainly) German, English and French, some of which are published here for the first time. It includes a full bibliography of the author's work, in addition to two indexes of classical authors and works, which aim to make accessible the remarkable riches that these Kleine Schriften have to offer. The three-volume collection, carefully selected by the author himself, offers over 150 texts organized primarily along Van Ess' own biography and the history of the discipline. It is divided into twelve parts, beginning with Tübingen where his career began in 1968, and ending with Retrospects and Postscripts for the future, with the thematic complexes Islam and its first options and Muʿtazila as centre pieces. All parts are introduced by brief accounts of the historical context in which each of the assembled texts was written and which course subsequent scholarship may have taken.